2019
DOI: 10.3758/s13428-019-01287-1
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of interpersonal interactions with continuous spatiotemporal data: Application to a study of the effects of resource competition on racial group interactions

Abstract: We describe a sequential qualitative ➔ quantitative mixed-method procedure used to construct conceptually grounded quantitative metrics of interpersonal behavior from continuous spatiotemporal data. Metrics were developed from data collected during an experiment in which racially diverse participants interacted with self-resembling avatars at social events hosted in the virtual world Second Life. In the qualitative stage, the researchers conceptualized four distinct patterns of movement from overhead video rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…For example, avatars (i.e., first-person perspective characters operated by the user) tended to hold realistic interpersonal distances, initiating interactions at approximately 5 virtual meters, and moving closer for more personal engagement (Friedman et al, 2007). Relevant to our study is research finding that avatars' racial appearance impacts social interactions (Eastwick & Gardner, 2009;Tawa et al, 2015Tawa et al, , 2020Vang & Fox, 2014); for example, avatars were more likely to comply with a request for a favor when approached by White compared to Black avatars (Eastwick & Gardner, 2009). Social justice educators may be particularly interested in the potential for virtual environments to offer students' embodiment experiences or interactive social experiences while operating an avatar with a visible identity that is different from one's own (e.g., a White person piloting a Black avatar).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…For example, avatars (i.e., first-person perspective characters operated by the user) tended to hold realistic interpersonal distances, initiating interactions at approximately 5 virtual meters, and moving closer for more personal engagement (Friedman et al, 2007). Relevant to our study is research finding that avatars' racial appearance impacts social interactions (Eastwick & Gardner, 2009;Tawa et al, 2015Tawa et al, , 2020Vang & Fox, 2014); for example, avatars were more likely to comply with a request for a favor when approached by White compared to Black avatars (Eastwick & Gardner, 2009). Social justice educators may be particularly interested in the potential for virtual environments to offer students' embodiment experiences or interactive social experiences while operating an avatar with a visible identity that is different from one's own (e.g., a White person piloting a Black avatar).…”
mentioning
confidence: 76%
“…A script was attached to each avatar and was used to measure social interaction, operationalized as the average number of avatars they interacted with at each 5-s interval over the duration of the trial. Conceptually, social interaction is a proxy measure of behavioral discomfort during intergroup interactions; previous research has found fewer avatar interactions during social events in Second Life to be correlated to intergroup anxiety (Tawa et al, 2020).…”
Section: Pve Embodiment For Social Justice Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…If not, research in those virtual game worlds is purely an end in itself. Results suggest that in fact, many behaviors are similar in online and offline contexts [ 7 , 10 12 ]. Researchers have approached this question from different angles.…”
Section: Introductionmentioning
confidence: 99%